Evaluation of a partnership between primary and secondary care providing an accessible Level 1 sexual health service in the community. (September 2014) - Kelly, Carmel; Johnston, Jillian; Carey, Fiona
Summary: Comprehensive testing for asymptomatic sexually transmitted infections in Northern Ireland has traditionally been provided by genitourinary medicine clinics. As patient demand for services has increased while budgets have remained limited, there has been increasing difficulty in accommodating this demand. In May 2013, the newly commissioned specialist Sexual Health service in the South Eastern Trust sought to pilot a new model of care working alongside a GP partnership of 12 practices. A training programme to enable GPs and practice nurses to deliver Level 1 sexual health care to heterosexual patients aged >16 years, in accordance with the standards of BASHH, was developed. A comprehensive care pathway and dedicated community health advisor supported this new model with close liaison between primary and secondary care. Testing for Chlamydia, gonorrhoea, HIV and syphilis was offered. The aims of the pilot were achieved, namely to provide accessible, cost-effective sexual health care within a framework of robust clinical governance. Furthermore, it uncovered a high positivity rate for Chlamydia, especially in young men attending their general practice, and demonstrated a high level of patient satisfaction. Moreover the capacity of secondary care to deliver Levels 2 and 3 services was increased.